Visceral adiposity loss is associated with improvement in cardiometabolic markers: findings from a dietary intervention study - Abdullah, Shazana Rifham; Nur Zati Iwani, Ahmad Kamil; Ahmad Zamri, Liyana; Wan Mohd Zin, Ruziana Mona; Abu Seman, Norhashimah; Zainal Abidin, Nur Azlin; Hamzah, Siti Sarah; Azizul, Nur Hayati; Omar, Azahadi; Seman, Zamtira; Yahya, Abqariyah; Md Noh, Mohd Fairulnizal (Frontiers in Endocrinology, 2025)
BackgroundVisceral adiposity is closely linked with cardiometabolic disorders, but evidence on the extent of visceral fat loss required for significant improvement in cardiometabolic markers remains limited. This study aims to investigate the association between visceral fat area (VFA) reductions and improvements in cardiometabolic markers following a 3-month dietary intervention.MethodsA total of 175 adults with overweight and obesity were involved in this non-randomized controlled trial. Data on sociodemographic, anthropometric, body composition and biochemistry were collected at baseline and after 3 months of intervention. The multiple logistic regression analysis was conducted to determine the association between VFA loss (no loss, < 5% loss, and ≥ 5% loss) and improvement in cardiometabolic markers. For each cardiometabolic marker, an improvement surpassing the minimum threshold of the third tertile was classified as a good improvement.ResultsCompared to those with no VFA loss, participants with VFA loss of ≥ 5% were significantly associated with a higher improvement in waist circumference (OR 2.97, 95% CI 1.16-7.64), high-density lipoprotein cholesterol (HDL-C) (OR 4.19, 95% CI 1.58-11.14), triglycerides (OR 3.01, 95% CI 1.14-7.92), and glycated hemoglobin (HbA1C) (OR 2.95, 95% CI 1.12-7.79). Other than that, those with < 5% VFA loss were 3.6 times more likely to have a higher improvement in HDL-C compared to those with no VFA loss (OR 4.08, 95% CI 1.36-12.22).ConclusionThis study found that the magnitude of VFA loss is an independent determinant of improvements in cardiometabolic markers and should be set as a clear target when designing obesity prevention programs.